2017
DOI: 10.2147/ndt.s139362
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of curdione against focal cerebral ischemia reperfusion injury in rats

Abstract: BackgroundCurdione is one of the most highly concentrated component of the active constituents in E-zhu, which has been reported to possess a variety of activities. However, the pharmacologic neuroprotective activity of curdione has not been evaluated. The present study aimed to investigate the protective effect of curdione on focal cerebral ischemia reperfusion-induced injury in rats and further exploring the underlying mechanisms.Materials and methodsAdult male Sprague Dawley rats were subjected to middle ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…It has been shown that treatment by antioxidant and anti-inflammatory agents has been able to impede sensorimotor dysfunction. [19][20][21] In this regard, our findings indicate that the antioxidant and anti-inflammatory activities of a-pinene are attributed to attenuation of neuronal injury and improvement in neurobehavioural functioning.…”
Section: Figurementioning
confidence: 67%
See 2 more Smart Citations
“…It has been shown that treatment by antioxidant and anti-inflammatory agents has been able to impede sensorimotor dysfunction. [19][20][21] In this regard, our findings indicate that the antioxidant and anti-inflammatory activities of a-pinene are attributed to attenuation of neuronal injury and improvement in neurobehavioural functioning.…”
Section: Figurementioning
confidence: 67%
“…In this test, 1 point was awarded for the inability to achieve the tasks or for the lack of a tested reflex. Additionally 13–18 points designated as severe injury, 7–12 points specified as moderate injury, and 1–6 points determined as mild injury …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also improved cognitive function and neuronal morphologic damage. In addition, it decreased MDA content and enhanced the activities of GSH‐PX, CAT, and SOD . Treatment with β‐elemene after the induction TBI by WDIAI model in rat improved NSS, and reduced TNFα, IL‐1β, apoptosis index, and expression of toll‐like receptor (TLR4), and casepase‐3.…”
Section: Resultsmentioning
confidence: 97%
“…Rhizoma Curcuma has been reported with antitumor effect [26], which mainly dependent on its essential oils. The effective bioactive compounds of the essential oils including: β-elemene, curcumol, curcumin, curdione, furanodiene, furanodienone, and germacrone have been reported with anti-platelet aggregation [27,28], anti-in ammatory [29], antibacterial [30], neuroprotective properties [31], prevent cardiotoxicity [32], and anti-tumor effect [26,30,[33][34][35][36]. Bene cial therapeutic effect of curdione has been reported in breast cancers [34], but the potential anti-cancer effect in uLMS and the underlying mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%